Robot-Assisted Surgery and the Nature of Remote Work: Lessons for Medicine From Other Fields. Issue 1 (June 2014) - Balkin, E. Asher; Kumar, Salil; Manko, Volodymyr; Jahn, Michelle A.; So, Joey; Antonik, Christopher
The result of a multi-year, multi-lab, interdisciplinary research project examining the impact of the introduction of robot-assisted surgical (RAS) technology into modern operating rooms, this presentation explores intra-corporeal RAS as a highly specialized, but not entirely unique working technique. Hundreds of hours of direct in-room observation, interviews with RAS surgeons at all levels of expertise from almost total novices to world-renowned experts have allowed the authors to recognize specific commonalities, particularly those dealing with changes in operator perspective, altered team roles, and coordination processes. In particular analogs between RAS, areal refueling, tower-crane construction work, and robotic arm control in space are presented. Most fundamentally, these four work situations are united by thee factors: the inability of the primary control operator to directly see the worksite, the need for high-precision coordination with colleagues, and the loss of situational awareness created by working in such environments. While RAS is relatively new, refueling teams, construction crews, and astronauts have been working under such conditions for much longer. As a result, this paper offers a series of best practice suggestions derived from other fields' experiences similar working conditions.